Impact Analysis of Cluster Front Line Demonstration on Yield and Economics of Summer Sesame under Western Region of Gujarat - Singh, Traloki; Dev, Rahul; Nautiyal, Pankaj; Sahu, Anjali; Singh, Mohit (International Journal of Bio-resource and Stress Management, 2025)
The study assessed the effectiveness of scientific cultivation techniques for sesame using improved varieties GT-4 and GJT-5 during 2021–2022 in Anjar, Bhuj, and Nakhatrana talukas of Kachchh district, Gujarat, India. Conducted over 11.6 hectares through 29 demonstrations by ICAR-CAZRI and Krishi Vigyan Kendra, Bhuj, India. The demonstration trials addressed the region’s saline-alkaline sandy soils with pH levels ranging from 8.5 to 9.2 and significant nutrient deficiencies. Sesame was sown between mid-February and early March and harvested from late April to early May. Improved practices included using high-yielding varieties, seed treatment, timely sowing, line sowing, recommended fertilizer application, and integrated pest management. The demonstrations achieved a 17.18% increase in seed yield, with 941 kg ha-¹ compared to 803.5 kg ha-¹ from farmers’ traditional practices. Technological gaps of 300 kg ha-¹ over two years highlighted the need for better soil management, irrigation, and seed quality to achieve potential yields. Extension gaps, ranging from 124 to 151 kg ha-¹, emphasized the importance of farmer education in adopting advanced agricultural methods. The technology index declined to 17.49%, reflecting improved feasibility and adoption of the innovations over time. Economic analysis showed demonstration plots had higher net returns (` 44,406 ha-¹) and a superior benefit-cost ratio (2.85) compared to local practices (` 30,133 ha-¹; B:C ratio 2.57). Post-demonstration, significant adoption of improved practices such as field preparation, fertilizer application, and pest management was observed. This study underscores the role of CFLDs in enhancing sesame productivity, economic returns, and farmer adoption of modern agricultural practices in challenging agro-climatic conditions.